The knowledge level teacher of physical education to adaptive physical education at Inklus Elementary Schools in Jetis Subdistrict Yogyakarta Regency - Fitria, Indah Rachmah; Kaloka, Pasca Tri (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2021)
This research aims to find out the level of knowledge of Physical Education teachers on Adaptive Physical Education in inclusive elementary schools located in Jetis District, Yogyakarta City. The research used the descriptive quantitative design with the survey method and used questionnaire as a means of data collection technique. The research subjects were the Physical Education teachers in Inclusive Elementary Schools located in Jetis, Yogyakarta with the total of 5 teachers. The data collection was using the true or false question items while the data analysis was assisted by Microsoft Excel and SPSS 25.0 program with the output in the form of percentages. The research results indicate that the level of knowledge of Physical Education teachers on adaptive Physical Education in Inclusive Elementary Schools in Jetis District, Yogyakarta City is in various levels as follows: in the very high level is at 0% (0 person), in the high level is at 40% (2 persons), in the medium level is at 20% (1 person), in the low level is at 40% (2 persons), and in the very low level is at 0% (0 person). Tingkat pengetahuan guru pendidikan jasmani terhadap penjas adaptif di Sekolah Dasar Negeri Inklusi Se-Kecamatan Jetis Kota Yogyakarta Penelitian skripsi ini memiliki tujuan untuk mengetahui tingkat pengetahuan guru pendidikan jasmani terhadap penjas adaptif di sekolah dasar negeri inklusi se- kecamatan jetis kota yogyakarta. Penelitian skripsi ini menggunakan desain penelitian dengan deskriptif kuantitatif dengan memakai metode survey dan teknik dalam pengumpulan data menggunakan kuesioner(angket), Subjek yang digunakan dalam penelitian ini adalah beberapa guru pendidikan jasmani yang berada di sekolah dasar negeri inklusi di kecamatan jetis kota yogyakarta yang berjumlah 5 guru pendidikan jasmani. Pengambilan data dalam penelitian ini menggunakan instrumen penelitian berbentuk beberapa soal dan memiliki alternatif jawaban benar salah, sedangkan untuk perhitungan data akhir menggunakan bantuan program Microsoft excel dan SPSS 25.0 dengan data presentase. Hasil penelitian skripsi ini menunjukkan bahwa diketahui tingkat pengetahuan guru pendidikan jasmani terhadap penjas adaptif di Sekolah Dasar Negeri Inklusi se- Kecamatan Jetis Kota Yogyakarta yang masuk pada kategori sangat tinggi sebesar 0 % (0 orang), pada kategori tinggi sebesar 40 % (2 orang), pada kategori cukup sebesar 20 % (1 orang), kategori kurang sebesar 40% (2 orang) dan kategori sangat kurang sebesar 0 % (0 guru).